Teleworking during the COVID-19 pandemic: The role of age in the relationship between technological anxiety and performance - Sousa, I.C.; Ramos, S.; Godinho, C.; Marques, T. (15th European Academy of Occupational Health Psychology Conference, 2022)
The COVID-19 pandemic enforced changes in the way people work. The extensive and mandatory adoption of telework, to allow compliance with lockdown measures and social distancing at work, brought numerous challenges for individuals and organizations (Belzunegui-Eraso & Erro-Garcés, 2020; Fana et al., 2020). Among these challenges, there is likely the need for workers to familiarize themselves with new or different technological tools while adapting to new ways of organizing their work (International Labour Organization [ILO], 2020). In this context, employers and managers are concerned about how potential barriers to the effective use of technologies (e.g., attitudinal, cognitive) can be detrimental to performance. Technological anxiety can be an individual barrier that interferes with performance. It refers to feelings of apprehension, tension, and even fear, regarding an individual’s ability to use technology-related tools (Meuter et al., 2003). Technological anxiety has been shown to affect technology use and the performance of computer-based tasks (Mahar et al., 1997). In addition, due to widespread stereotypes about older individuals’ lack of technological proficiency (Harris et al., 2018), adaptation to new technology required by teleworking might have a greater impact on the performance of these workers. Managerial views of older workers often include that they are less able or less willing to learn and to adopt new technology than younger workers (Sharit et al., 2009). A study from Gray and McGregor (2003) showed that older workers were seemingly in agreement with their employers about their fear of new technology, which supports a key stereotype against older individuals. Therefore, the aim of this study was to explore the role of age on the relationship between technological anxiety and perceived performance. We hypothesized that the negative influence of technological anxiety on performance will be greater for older workers. To test this hypothesis, a repeated cross-sectional design is being used, which allows the examination of time-varying relationships. The first data collection was between January and February of 2021 when teleworking was mandatory whenever possible. The second data collection is scheduled for January 2022. In the first study, a sample of 906 workers, aged between 20 and 66 years old (M = 37.56, SD = 11.46), completed an online questionnaire. Findings show that the proposed model is significant (F(4,901) = 24.231, p < .001), and age moderates the effect of technological anxiety on perceived performance (B = .008, 95% CI [.002, .013]). However, contrary to expectations, this effect was significant for younger workers (B = -.262, 95% CI [-.360, -.164]) but not for the older workers (B = -.090, 95% CI [-.188, .008]). These results can likely be explained by the limited work experience of younger workers. Work experience is associated with the accumulation of knowledge and skills that enhance workers’ adaptability. Thus, older workers may have already identified strategies for closing their gaps in technology skills, increasing their self-confidence in using technology tools and resources. This first study contributes to demystify stereotypes about older workers’ fear regarding technological changes as a deterrent to performance.